Perturbations to the lower ionosphere by tropical cyclone Evan in the South Pacific Region. Issue 8 (3rd August 2017) - Kumar, Sushil; NaitAmor, Samir; Chanrion, Olivier; Neubert, Torsten
Abstract: Very low frequency (VLF) electromagnetic signals from navigational transmitters propagate worldwide in the Earth‐ionosphere waveguide formed by the Earth and the electrically conducting lower ionosphere. Changes in the signal properties are signatures of variations in the conductivity of the reflecting boundary of the lower ionosphere which is located in the mesosphere and lower thermosphere, and their analysis is, therefore, a way to study processes in these remote regions. Here we present a study on amplitude perturbations of local origin on the VLF transmitter signals (NPM, NLK, NAA, and JJI) observed during tropical cyclone (TC) Evan, 9–16 December 2012 when TC was in the proximity of the transmitter‐receiver links. We observed a maximum amplitude perturbation of 5.7 dB on JJI transmitter during 16 December event. From Long Wave Propagation Capability model applied to three selected events we estimate a maximum decrease in the nighttime D region reference height ( H′ ) by 5.2 km (13 December, NPM) and maximum increase in the daytime D region H′ by 6.1 km and 7.5 km (14 and 16 December, JJI). The results suggest that the TC caused the neutral densities of the mesosphere and lower thermosphere to lift and sink (bringing the lower ionosphere with it), an effect that may be mediated by gravity waves generated by the TC. The perturbations were observed before the storm was classified as a TC, at a time when it was a tropical depression, suggesting the broader conclusion that severe convective storms, in general, perturb the mesosphere and the stratosphere through which the perturbations propagate. Key Points: Strong day and nighttime VLF signal anomalies associated with December 2012 TC Evan The maximum increase in the daytime D region VLF reference height by 7.5 km Morlet wavelet analysis of VLF signal amplitude gives strong wave‐like signatures associated with this TC